2012
DOI: 10.5946/ce.2012.45.1.95
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Endoscopic Treatment for Gastrocolocutaneous Fistula as a Complication of Percutaneous Endoscopic Gastrostomy

Abstract: As a rare complication of percutaneous endoscopic gastroscopy (PEG), a gastrocolocutaneous fistula may occur after PEG placement. This paper reports an interesting case which PEG tube unintentionally penetrated transverse colon during PEG. A 72-year-old female patient who suffered from medullary infarction underwent PEG procedure for enteral nutrition, and fecal materials were observed 6 days after the procedure. Transverse colon located in antero-superior site of stomach was observed through abdominal compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Recently, endoscopic treatment of fistulas has been attempted, although surgery is often required. 16 , 17 , 18 In our first case, the gastrocolic fistula was successfully sealed using metal clips during colonoscopy, and the colocutaneous fistula spontaneously closed.…”
Section: Discussionmentioning
confidence: 84%
“…Recently, endoscopic treatment of fistulas has been attempted, although surgery is often required. 16 , 17 , 18 In our first case, the gastrocolic fistula was successfully sealed using metal clips during colonoscopy, and the colocutaneous fistula spontaneously closed.…”
Section: Discussionmentioning
confidence: 84%
“…There have been attempts at endoscopic treatment of fistulae after removal of PEG tube ( Table 2 ) [ 4 , 7 , 9 , 15 - 20 ]. Hwang et al suggested that endoscopic treatments would be helpful in cases where the fistula does not spontaneously close within several days [ 17 ]. Kim et al suggested that endoscopic closure would accelerate the blockage of the fistula in patients with a risk of delayed wound healing and infection (e.g., diabetes mellitus) [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The method of endoscopic treatment is likely determined according to the size of the fistula opening. Small fistula tracts were treated only with hemoclips, but detachable snare with clips, over-the-scope clip, and cardiac septal defect closure device have been used for relatively large fistula openings [ 4 , 9 , 17 - 20 ]. In our case, we used hemoclips to close the fistula, and argon plasma coagulation was performed before clipping to help mucosal adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…• When fistula does not close spontaneously even after conservative treatment. 15 • Patients where delayed wound healing and infection is expected. 4 • Large fistulous opening which definitely needs surgical intervention.…”
Section: Discussionmentioning
confidence: 99%